“El fabricante de honradez", de Ramón y Cajal: humor, positivismo y voluntad - Ramírez del Pozo Martín, José Manuel (El Colegio de México, 2023)
The scientific research carried out by Ramón y Cajal, the winner of the Nobel Prize in Physiology or Medicine in 1906, was decisive in estab-lishing the basis of neuroscience. Although he has been lauded as one of the most important intellectual figures in 20th century Spain, his fictional work has received little attention. This paper uses the theory of critical discourse to analyze and interpret “The manufacturer of honor”, a short-story which offers the reader both a parody on pseudo-science and a meditation on the relationship of science to society and morality.